Hydrogen sulfide induces systemic tolerance to salinity and non-ionic osmotic stress in strawberry plants through modification of reactive species biosynthesis and transcriptional regulation of multiple defence pathways - Christou, Anastasis; Papadopoulos, Ioannis; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2013)
Hydrogen sulfide (H2S) has been recently found to act as a potent priming agent. This study explored the hypothesis that hydroponic pretreatment of strawberry (Fragaria × ananassa cv. Camarosa) roots with a H2S donor, sodium hydrosulfide (NaHS; 100 μM for 48h), could induce long-lasting priming effects and tolerance to subsequent exposure to 100mM NaCI or 10% (w/v) PEG-6000 for 7 d. Hydrogen sulfide pretreatment of roots resulted in increased leaf chlorophyll fluorescence, stomatal conductance and leaf relative water content as well as lower lipid peroxidation levels in comparison with plants directly subjected to salt and non-ionic osmotic stress, thus suggesting a systemic mitigating effect of H2S pretreatment to cellular damage derived from abiotic stress factors. In addition, root pretreatment with NaHS resulted in the minimization of oxidative and nitrosative stress in strawberry plants, manifested via lower levels of synthesis of NO and H2O2 in leaves and the maintenance of high ascorbate and glutathione redox states, following subsequent salt and non-ionic osmotic stresses. Quantitative real-time RT-PCR gene expression analysis of key antioxidant (cAPX, CAT, MnSOD, GR), ascorbate and glutathione biosynthesis (GCS, GDH, GS), transcription factor (DREB), and salt overly sensitive (SOS) pathway (SOS2-like, SOS3-like, SOS4) genes suggests that H2S plays a pivotal role in the coordinated regulation of multiple transcriptional pathways. The ameliorative effects of H2S were more pronounced in strawberry plants subjected to both stress conditions immediately after NaHS root pretreatment, rather than in plants subjected to stress conditions 3 d after root pretreatment. Overall, H2S-pretreated plants managed to overcome the deleterious effects of salt and non-ionic osmotic stress by controlling oxidative and nitrosative cellular damage through increased performance of antioxidant mechanisms and the coordinated regulation of the SOS pathway, thus proposing a novel role for H2S in plant priming, and in particular in a fruit crop such as strawberry.
Keywords: Vitamin C; Glutathione; Hydrogen sulfide